Analysis of Social Trust and Subjective Welfare in Poland - Mariola Sasinowska (Institute of Economic Research (IER), 2017)
Research background: The article is primarily based on the research in the field of welfare economics, utility theory, social capital and econometrics. In the paper are discussed articles such authors as Bjornskov, Easterlin, Ravallion and Uslaner. Purpose of the article: The purpose is to explore the generalized social trust and subjective welfare of Poles and to their relationship. According to the author's knowledge, such extensive research like this for Poland has not been yet conducted. Methodology of the article: Data sample used in the research comes from the project "Wycena, Aspekty Sprawiedliwosci i Preferencje Wzgledem Odnawialnych Zrodel Energii i ich lokalizacji w Polsce i w Niemczech" which was carried out with the support of the National Science Center. Econometric model was prepared based on the least squares method and the ordered probit model. Findings & Value Added: The main outcome of this paper is confirmed importance of the relationship between social trust and the subjective welfare of Poles. Furthermore, it has been proven that both social trust and subjective wealth can be linked both to income and non-income related factors such as inequality and education.
Keywords: D1; D6; I3; 330; welfare economy; subjective economic welfare; social trust; ordered probit model